The Metaphysics of theism : Aquinas's natural theology in Summa contra gentiles 1 - Kretzmann, Norman (Oxford : Clarendon Press, 1997)
The Metaphysics of Theism presents an explanation and evaluation of Aquinas's natural theology, the paradigm of which is the first book of the Summa contra gentiles. But in addition to considering this as a monumental achievement of medieval philosophy, Norman Kretzmann approaches it as a continuing enterprise that can be developed with considerable benefit in contemporary philosophy. Professor Kretzmann argues that natural theology offers the most appropriate route by which philosophers can, as philosophers, approach theological propositions, and that the one presented in this book is the best available natural theology.
Theology from the bottom up --The God of the self-movers --The existence of Alpha --From independence to perfection --From perfection to infinity --Intellect --Will --Joy, love, and liberality.
Includes bibliographical references and index
Keywords: Thomas, Aquinas, Saint, 1225?-1274. Summa contra gentiles; Metaphysics; Theism; Natural theology